2015
DOI: 10.1016/j.ijscr.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of spleen: a case report

Abstract: HighlightsWe present a case of nflammatory pseudotumor of spleen.It is an extremely rare condition of unknown etiology.It is considered as a benign lesion with multiple differential diagnoses.Splenectomy is indicated to confirm diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Inflammatory pseudotumors are rare masses of inflammatory cells that can be found in various anatomical areas of the body. 4-7 The name inflammatory pseudotumor was first coined in 1954 by Umiker and Iverson, 8 , 10 and encompasses a spectrum of inflammatory lesions including plasma cell granuloma, plasma cell pseudotumor and myofibroblastic tumor, which are all thought to arise from a similar underlying inflammatory disease process, eventually resulting in a tumor like mass of inflammatory cells. 7 , 8 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory pseudotumors are rare masses of inflammatory cells that can be found in various anatomical areas of the body. 4-7 The name inflammatory pseudotumor was first coined in 1954 by Umiker and Iverson, 8 , 10 and encompasses a spectrum of inflammatory lesions including plasma cell granuloma, plasma cell pseudotumor and myofibroblastic tumor, which are all thought to arise from a similar underlying inflammatory disease process, eventually resulting in a tumor like mass of inflammatory cells. 7 , 8 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Other etiologies including trauma with secondary focal parenchymal necrosis, chronic infection, low-grade neoplastic processes, vascular causes and immunological derangement have been suggested. 1 , 2 , 4 , 6 , 10 This is still a topic of discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory pseudotumor (IPT) of the spleen is an extremely rare tumor-like lesion with approximately <115 published cases in adults until 2015, and probably not more than 116 cases until year 2017, at the best of our knowledge [1], [2], [3], [4], [5], [6]. This entity was first introduced in 1984 by Cotelingam and Jaffe [1].…”
Section: Introductionmentioning
confidence: 99%
“…This entity was first introduced in 1984 by Cotelingam and Jaffe [1]. It is a lesion composed of proliferated spindle cells with admixed inflammatory cellular component of variable composition including lymphocytes, plasma cells, histiocytes, and granulocytes [1], [2], [3], [4], [5], [6]. Additional studies have demonstrated that spindle cells are in fact myofibroblasts, prompting the designation inflammatory myofibroblastic tumor (IMT) [2].…”
Section: Introductionmentioning
confidence: 99%